Impact of plasticizer addition on molecular properties of polybutadiene rubber and its manifestations to glass transition temperature - Sharma, Pragati; Roy, Sudip; Karimi-Varzaneh, Hossein Ali (Macromolecular Theory and Simulations, 2019)
Effect of blending low and high T-g polymer on the structural, spatial, and temporal properties of the polybutadiene rubber are investigated using molecular dynamics simulations. It is elucidated that smaller chain length counterpart of polybutadiene (5mer-OB) acts as plasticizer for the polybutadiene rubber matrix (32mer-PB). Observed flexibility at macroscopic level by plasticizer addition is corroborated at the molecular level in the form of lower conformational rigidity and faster diffusion of polybutadiene chains in the mixtures. It is inferred that plasticizers decreases T-g of the matrix, due to cooperative influence of decreased chain packing and rigidity. Opposite effect is observed in mixtures with high T-g polymer, polystyrene. T-g of the mixtures showed substantial dependence on the type, concentration, chain length as well as miscibility of plasticizers in the matrix. However, the effect of increasing chain length is more pronounced but counter-controlled by the spatially heterogeneous distribution of the plasticizer. Clustering of polystyrene chains induced significant dynamic heterogeneity in the homogeneous polybutadiene matrix, which apparently lead to reduced plasticization effect. Addition of plasticizers in rubber induce discernible changes in the structural and dynamic properties of the rubber matrix, which manifest as the variation in glass transition and explains the real-life activity of plasticizers.
Keywords: Glass transition temperature; MD Simulation; plasticizer action; polybutadiene rubber; Polystyrene; spatial and dynamic heterogeneity